2018
DOI: 10.1177/1065912918772681
|View full text |Cite
|
Sign up to set email alerts
|

Marching Orders? U.S. Party Platforms and Legislative Agenda Setting 1948–2014

Abstract: What is the relationship between the priorities expressed in party platforms before an election and the subsequent legislative agenda? The agenda setting literature often deemphasizes the role of political parties in agenda setting, instead focusing on the importance of problems bubbling up to the surface and demanding attention from policymakers. However, parties will often express different issue priorities during elections, and compete based on those priorities. If those promises are credible, voters should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
12
0
3
Order By: Relevance
“…We should expect a dynamic relationship between the two branches of government. For example, many agenda‐setting studies have observed that parties and executives can influence legislative agendas in Western countries (see Fagan, 2018; Lovett et al, 2015; Mortensen et al, 2011).…”
Section: Mapping Executive Attention In Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…We should expect a dynamic relationship between the two branches of government. For example, many agenda‐setting studies have observed that parties and executives can influence legislative agendas in Western countries (see Fagan, 2018; Lovett et al, 2015; Mortensen et al, 2011).…”
Section: Mapping Executive Attention In Brazilmentioning
confidence: 99%
“…Baumgartner, Jones, and their numerous collaborators used these data to test successfully PET predictions in the United States, finding that various forms of cognitive and institutional friction cause policy change to become more or less punctuated (Jones & Baumgartner, 2005; Jones, Larsen‐Price, & Wilkerson, 2009; Jones, Sulkin, & Larsen, 2003; Jones, Thomas, & Wolfe, 2014). Furthermore, these data have been used to examine why changes in the distribution of attention to policy in the United States occur, such as presidents using speeches to direct attention (Lovett, Bevan, & Baumgartner, 2015), changes in the interest‐group system (Leech et al, 2005), party platforms promising to emphasize issues (Fagan, 2018), and constituent representation (Miler, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, os programas de governo poderiam ser entendidos como mecanismos pelos quais se vincula eleitores aos representantes eleitos, ou seja, caso os partidos nos governos não representem as prioridades prometidas, o conflito eleitoral entre os partidos não estruturaria o conflito político no governo sobre as agendas políticas (FAGAN, 2018).…”
Section: Com a Consolidação Dos Sistemas Partidários Após O Processounclassified
“…Para Fagan (2018), a relação entre a plataforma e a agenda do Congresso varia de acordo com o assunto, tipo de agenda e alinhamento ao governo, indicando que políticas enfatizadas na plataforma do partido podem prever questões enfatizadas no Congresso, mas apenas imediatamente após a eleição presidencial. Deste modo, a análise da congruência entre a construção da agenda legislativa dos deputados de um partido em seu primeiro mandato para Câmara dos Deputados, como o partido NOVO, a partir de seu programa eleitoral, contribui para a compreensão dos fatores e elementos no debate que estabelece uma relação entre a existência de partidos políticos com um conteúdo programático e ideológico mais ou menos definido.…”
Section: Introductionunclassified